Modi's economics - Acharya, Rajeshkumar; Tanna, Girishchandra (Ahmedabad Nanoland, 2019)
Narendra Damodardas Modi, a Name buzzing across the world. It is his concrete work for development and welfare of all as Prime Minister that created a niche for himself in the hearts of the people.
Keywords: Politics and government; Economic development; Economic policy